Intelligent Decision Support System in the Selection of Children's School Types Based on IQ, SQ, and EQ in Aceh - Cut Fadhilah; Nunsina Nunsina; Rosma Siregar (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Schools are institutions for students to carry out early stages of education that are tailored to their level. Developments that continue to show their existence have a very rapid impact, for example school institutions. Currently, there are permanent schools (pondok/pesantren) or public schools (state/private) with their respective performances. However, the tendency of parents to choose the best school according to him without paying attention to the child's growth and development first. This often occurs after the transition from elementary school to junior high school (SMP). Especially for the Aceh area, where the majority of children are directly in hostel with the hope that the child can grow optimally without reviewing the advantages and disadvantages. The rapid development of technology in Indonesia has contributed a lot to the problems experienced by society with the birth of various kinds of intelligent systems. The development of an intelligent system based on this expert system can be a solution to the problems that arise for parents now, can determine the type of school children will go to in the future. by implementing a method that is able to make decisions by providing the best solution. The purpose of this study is to build an intelligent system that is able to provide decision support in determining the type of school. By providing services to parents in the form of a web service-based interface system. As well as understanding the type of child's ability before deciding to be in a boarding school or public school, especially at the junior high school level.